Essays on culture, institutions and comparative development - Wang, Jun (Nanyang Technological University, 2023)
The interactions between culture and economic development have garnered growing attention in the literature. A variety of cultural traits and individual preferences have been found to be deeply rooted in people’s subsistence and productive activities. Meanwhile, due to the insufficient knowledge and technology to overcome natural barriers in history, such activities largely depended on region-specific environments and resources. In a constant attempt to optimize the utility under localized constraints, people experience a transition of customs and beliefs toward the direction that favors the improvement of their productivity and life quality. These traditions have been highly persistent across generations and in turn affect the trajectory of a region’s comparative development by shaping people’s behavior in extensive aspects. In this evolution process, the coordination in the household, community, and societies also plays an important role since it generates additional advantages through collectivist efforts and resource sharing. The requirement of systematically organizing cooperative activities and allocating resources on a large scale could give rise to the emergence of specialized institutions and even the reinforcement of the overall state capacity. Therefore, understanding the spiral of economic, cultural, and institutional changes is crucial for explaining a region’s comparative performance as well as the disparity across space. In this thesis, we focus on how people develop new cultural values and form institutions in response to external environments, and how these changes will exert further socioeconomic impacts. It consists of three self-contained essays that explore the relevant topics, thus contributing to the literature by uncovering the origins of certain essential social norms or the interrelations between institutional and economic growth in a society. Besides, since we have utilized China as a natural testing ground, the findings also help us enhance the understanding of this vast emerging nation. In Chapter 1, we investigate the impact of historical disease burden on the development of contemporary China. Using historical records for nearly six centuries, we construct a county-level dataset for the distribution of epidemics in China. We find that historical disease pressure has a favorable impact on economic development in the long run. This positive association holds up to a series of robustness checks. Additionally, we find that earlier institutional development in disease control is an effective channel since the establishment of disease prevention centers facilitated an early adoption of modern disease control systems, which in turn improved public health, education, and productive activities. In Chapter 2, we turn to another considerable survival threat for humans, namely natural disasters. We examine the origin of long-term orientation (LTO) by exploiting the variation in historical exposure to significant disasters. We combine disaster data with multiple World Values Survey and European Values Survey waves to test two opposing hypotheses built upon economic and psychological theories. We find robust evidence at multiple levels supporting the view that larger exposure to catastrophic events increases the degree of LTO, and the psychological process of future-oriented coping is a mechanism that helps explain this result. To cope with adverse events, individuals undertake cognitive and behavioral actions that prioritize the long term, thus shedding light on the formation of time preference. Chapter 3 examines the effect of labor demand in traditional farming on contemporary gender equality in China. We hypothesize that in regions traditionally exposed to agro-climatic environments favoring the cultivation of more labor-intensive crops, there is a stronger motivation for female members to share the farmwork. Using county-level data on labor input required to farm crops for China, we find that higher demand for agricultural labor results in more balanced sex ratios at birth and other gender-equitable outcomes today. Women’s participation in agricultural production increases their contribution to household income, which improves their status in society. This gradually changes traditional gender role beliefs, leading to a preference for more balanced gender roles today. Lastly, in Chapter 4, we provide an overall conclusion and policy implications based on the findings of the three main chapters.